Some ways to increase learning possibilities for full and hard-hearing people - Zajančkauskienė, Lina (Lietuvos matematikos rinkinys, 2008)
Lithuanian educational strategic provision states that the present poses completely new social, pedagogic and subject requirements for teachers; they must have good information and communication skills. Therefore, we should help teachers, provide relevant materials for education, and allow them to learn the newest things. The paper deals with problems of teaching pupils that have special needs – dull and hard-hearing pupils and ICT for teaching them. Some possibilities and problems are discussed – ICT integration into learning progress, problems that may occur while applying the program „Link-it“, problems while localizing similar software for dull and hard-hearing people.
Keywords: special needs education; information technology; localization; ICT